Reconstructive memory and the impact of technology in Ted Chiang’s The Truth of Fact and Anxiety is The Dizziness / Yuchuan Zheng - Yuchuan , Zheng (2023)
Fallible and reconstructive memory has been frequently interpreted in science fiction stories and examined in studies as a major drawback that is inferior to digitalized memory and vulnerable to capitalist manipulation. There are still insufficient studies about technology’s non-capitalist and humanistic impacts on human reconstructive memory. American author Ted Chiang’s novellas The Truth of Fact, the Truth of Feeling and Anxiety is the Dizziness of Freedom reveal reconstructive memory’s unobtrusive nature and delve into the humanistic impacts of technology on people’s cognition and relationships. This research examines how Chiang embeds his postulation about technology’s humanistic impacts in his narrative thought experiments in the form of fiction, in which he creates an intense and dynamic interaction between science fiction devices and multiple characters. Applying Frederic Bartlett’s theory of Reconstructive Memory and the theory of Reading Fiction as Thought Experiments, this dissertation focuses on two main characters the father and Dana’s cognitive transformations having interacted with science fiction devices Remem and Prism, elucidating the complicated mutual influences between technology and human reconstructive memory. Chapters two and three discover that these science fiction devices represent sharp-end technology with rich symbolic meanings and are essential tools of Chiang’s narrative thought experiments. This dissertation also found that these science fiction devices engender schematic changes in characters, allowing them to reappraise their attitude toward a guilty relationship. This study contributes to a humanistic and nuanced approach to technology in science fiction stories which is addressed as techno-realism, and stimulates rumination over technology’s humanistic impacts on human reconstructive memory and a possible direction for the development of memory-modulating technology.